Comparative anti-methanogenic ability of green algae (C. reinhardtii) with/without nanoparticles: in vitro gas and methane production - Palangi, Valiollah; Kaya, Adem; Macit, Muhlis; Nadaroglu, Hayrunnisa; Ünlü, Hayrullah Bora; Kaya, Ali; Fekri, Ashkan; Mammadov, Ayaz; Lackner, Maximilian (Frontiers in Veterinary Science, 2025)
IntroductionThe purpose of this study was to investigate how in vitro gas production (GP) and ruminal fermentation characteristics were affected by increasing concentrations of green algae plant (C. reinhardtii) extracts in combination with nanoparticles MgO and MgS.MethodsA solution containing 0.1 M MgCl2 was prepared in 300 mL for the green production of MgCl nanoparticles. The mixture was refluxed for two hours at 85°C using a reflux condenser after 10 mL of pomegranate plant extract was added. The green algal plant (C. reinhardtii), which has many non-toxic antioxidants, was used as a carbon source to produce carbon quantum dots (CQD). Chemical analysis was conducted in accordance with AOAC (2005) recommendations. Rumen fluid from recently slaughtered calves is used to produce in vitro gas immediately following slaughter. Analysis of variance (ANOVA) was performed on the obtained data from the in vitro study in a completely randomized design using the mixed model of SAS (version 9.4; Inc., Cary NC, USA).Results and DiscussionThe variance analysis results and the average values of the chemical compositions were significantly influenced by the extracts (all p < 0.0001). In this line, the values of net gas, pH, OMD, ME, NEl, and ME were found to be the highest for Algae + 50 MgO and the lowest for Algae + 50 MgS, respectively (all p < 0.0001). These promising results imply that extracts from C. Reinhardtii may be able to mitigate the adverse consequences of rumen fermentation. To precisely ascertain the impact particular Rhodophyta on greenhouse gas emissions, additional investigation is needed.